A Nordic registry-based study of drug treatment patterns in overactive bladder patients. (4th July 2019) - Milsom, Ian; Schiotz, Hjalmar A.; Svensson, Maja; Kilany, Suzanne; Hansson, Fredrik
Abstract: Aim: To describe treatment patterns in Denmark, Norway and Sweden for patients receiving overactive bladder (OAB) pharmacotherapy. Methods: This was a prospective, multinational, registry-based study involving three nationwide prescribed drug registries (sample size 6000 patients per country), performed between 1 January and 30 June 2014. Patients were followed prospectively for 12 months after first pick-up of index medication. The primary objective was to evaluate the proportion of patients picking up first refill of index medication. Secondary objectives included evaluation of the average number of pick-ups collected during 1 year and time to discontinuation of index medication. Results: A high proportion of patients in the three Nordic countries picked up a first refill of OAB medication: 64–75% for mirabegron and 84–95% for individual antimuscarinics. Amongst treatment-naïve patients, the proportion picking up their first mirabegron refill was 60–64%; for individual antimuscarinics it was 30–63%. Mean number of pick-ups during 1 year ranged from 3.5–5.0 for mirabegron across the countries and for individual antimuscarinics from 3.8–12.3. Median time to discontinuation for mirabegron ranged from 140 (Denmark) to 207 days (Norway) and, for individual antimuscarinics (solifenacin), from 182 (Denmark) to 355 days (Sweden). At 12 months, the proportion of patients still on treatment with mirabegron and antimuscarinics was 21% and 38%, respectively. Conclusions: Treatment patterns in patients with OAB picking up a mirabegron or antimuscarinic prescription in Denmark, Norway and Sweden indicate that persistence remains a challenge.